Zinc supplementation in preterm infants and growth indicators in a developing country - Kaban, Risma Kerina; Azis, Henri; Prawitasari, Titis; Kautsar, Ahmad; Lusyati, Setya Dewi; Insani, Nadia Dwi (Paediatrica Indonesiana, 2023)
Background Zinc is one of the micronutrients that is found deficient in preterm infants. To date, no parenteral zinc supplements are available in Indonesia and there is no recommendation established for routine zinc supplementation in preterm infants. Objective To evaluate the impact of zinc supplementation on growth indicators and morbidity in preterm infants. Methods This double-blind, randomized controlled trial included preterm infants aged 28-32 weeks who were assigned to one of two groups: the first group received a 10 mg zinc supplementation, while the second (control) group received a placebo. At discharge or at a maximum of 40 weeks post-menstrual age (PMA, calculated from the first day of the mother's last menstrual period), the following were evaluated : growth indicators (weight, length, and head circumference), serum zinc level, zinc supplementation side effects, and morbidity rate (intraventricular hemorrhage/IVH, necrotizing enterocolitis/NEC, btonchopulmonary dysplasia/BPD). Data were analyzed with independent T-test using SPSS version 22 software. Results Seventy-eight subjects were assigned to the zinc supplementation group and 76 subjects were assigned to the placebo group. Serum zinc level and mean body weight increment were significantly higher in the zinc group compared to the placebo group (P=0.00 and P=0.02, respectively). There were no significant differences between groups in mean body length or head circumference increment, nor in morbidity rate. Conclusion Preterm infants who received zinc supplementation have higher serum zinc level and mean body weight increment compared to the placebo group. No side effects are observed to have been caused by zinc supplementation.